Determinan Transparansi Pelaporan Keuangan Organisasi Perangkat Daerah - Riska Riska; Nina Yusnita Yamin; Jurana Nurdin (Universitas Muhammadiyah Jakarta, 2022)
This study aims to analyze the determinants of financial reporting transparency implementation in Regional Apparatus Organizations (RAO). The study employs quantitative approach with population of RAO in Pasangkayu Regency, West Sulawesi; with saturation sampling technique, we explore respondents which are the head of finance and program sub-division. We use multiple linear regression to analyze our data. The results show that external pressure, environmental uncertainty, and management commitment have positive effect on the implementation of financial reporting transparency.